2019
DOI: 10.1104/pp.19.01300
|View full text |Cite
|
Sign up to set email alerts
|

Apple ALMT9 Requires a Conserved C-Terminal Domain for Malate Transport Underlying Fruit Acidity

Abstract: Malate accumulation in the vacuole largely determines apple (Malus domestica) fruit acidity, and low fruit acidity is strongly associated with truncation of Ma1, an ortholog of ALUMINUM-ACTIVATED MALATE TRANSPORTER9 (ALMT9) in Arabidopsis (Arabidopsis thaliana). A mutation at base 1,455 in the open reading frame of Ma1 leads to a premature stop codon that truncates the protein by 84 amino acids at its C-terminal end. Here, we report that both the full-length protein, Ma1, and its naturally occurring truncated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 63 publications
0
47
0
Order By: Relevance
“…Malate is a pivotal metabolite that is involved in regulating osmotic pressure, pH homeostasis, and stress resistance, and it significantly influences fruit quality 2,7 . A previous study has shown that the BTB-BACK-TAZ protein MdBT2 ubiquitinates the bHLH TF MdCIbHLH1 to regulate malate accumulation and vacuolar acidification 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malate is a pivotal metabolite that is involved in regulating osmotic pressure, pH homeostasis, and stress resistance, and it significantly influences fruit quality 2,7 . A previous study has shown that the BTB-BACK-TAZ protein MdBT2 ubiquitinates the bHLH TF MdCIbHLH1 to regulate malate accumulation and vacuolar acidification 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, whether MdBT2 affects malate accumulation through MdMYB1 still needs further study. The role of MdALMT9 in regulating malate accumulation has been clearly demonstrated 2,5,7,20 , and MdMYB73 regulates malate accumulation by activating the transcription of MdALMT9 (ref. 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success could be attributed to the choice of the mapping population GMAL 4595 and the adaptation to the AFDDD mapping approach. Population GMAL 4595 was previously used for fine genetic mapping of Ma, leading to the identification of the critical premature stop codon mutation in Ma1 that was causal for low acidity 4,14,17 . One of the important characteristics of population GMAL 4595 was the non-detectable effect of Ma3 on chromosome 8, making it highly suitable for detection of other genes controlling high acidity in the background of Ma-.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic cause for low acidity had been attributed to the premature stop codon leading mutation from G to A at base 1455 in the Ma1 open reading frame (ORF), which effectively truncates 84 amino acids at the MA1 C-terminus, presumably creating a malfunctioned MA1 14 . Indeed, a latest study demonstrates that the C-terminus of MA1 is essential for malate transport as the Ma1-1455A (allele ma1) protein showed significantly lower malate transport activity than the Ma1-1455G (Ma1) protein when expressed in both Xenopus laevis oocytes and Nicotiana benthamiana cells 17 .…”
Section: Introductionmentioning
confidence: 99%